2022
DOI: 10.3389/fmed.2022.943596
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative hypotension in non-emergency decompression surgery for cervical spondylosis: The role of chronic arterial hypertension

Abstract: BackgroundCervical spondylotic myelopathy and chronic hypertension show a cause-effect relationship. Hypertension increases cardiovascular risk and is associated with intraoperative hypotension. We aimed to evaluate intraoperative hypotension in patients undergoing non-emergency decompression surgery for cervical spondylosis and its association with clinical myelopathy and chronic arterial hypertension.MethodsThis retrospective cohort study used healthcare data of adult patients undergoing cervical spine surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(47 reference statements)
0
2
1
Order By: Relevance
“…16 17 In a retrospective analysis of cervical spine surgery for cervical spondylosis, Chiang et al reported 43.4% incidence of intraoperative hypotension and was associated more in older patients, male sex, chronic hypertension, and increased number of spine segment treated. 18 The incidence of intraoperative hypotension in the current study was lower (26.7%) from that reported by Chiang et al It may be due to the fact that the level of surgery was not restricted to cervical spine only and the pathologies also varied. The hypothesized etiologies are overdosage of the induction agent (when calculated according to the lean body weight) and the unique physiological changes in the cardiovascular system of patients with obesity contributing to cardiomyopathy (e.g., hypervolemic state with venous hypertension, myocardial hypertrophy, diastolic dysfunction, and biventricular dilatation) along with preexisting preoperative dehydration.…”
Section: Discussioncontrasting
confidence: 70%
“…16 17 In a retrospective analysis of cervical spine surgery for cervical spondylosis, Chiang et al reported 43.4% incidence of intraoperative hypotension and was associated more in older patients, male sex, chronic hypertension, and increased number of spine segment treated. 18 The incidence of intraoperative hypotension in the current study was lower (26.7%) from that reported by Chiang et al It may be due to the fact that the level of surgery was not restricted to cervical spine only and the pathologies also varied. The hypothesized etiologies are overdosage of the induction agent (when calculated according to the lean body weight) and the unique physiological changes in the cardiovascular system of patients with obesity contributing to cardiomyopathy (e.g., hypervolemic state with venous hypertension, myocardial hypertrophy, diastolic dysfunction, and biventricular dilatation) along with preexisting preoperative dehydration.…”
Section: Discussioncontrasting
confidence: 70%
“…Third, despite random allocation of patients, differences were observed in terms of weight and the number of patients with diabetes mellitus. However, the differences in weight were not clinically significant, and it is unlikely that the presence of diabetes had a decisive impact on the results of our study [ 31 ].…”
Section: Discussionmentioning
confidence: 95%
“…Our study confirms findings from previous studies, which indicated a close relationship of prolonged surgery and increased blood loss to intraoperative hypotension[ 4 , 16 , 17 ]. The risk of intraoperative hypotension escalates with age, especially in older patients, likely attributable to diminished cardiac function, reduced vascular elasticity from atherosclerosis, and decreased sympathetic nerve sensitivity, which impair blood pressure regulation[ 18 - 20 ]. Extended surgery and significant blood loss are indicative of substantial surgical trauma, resulting in prolonged anesthesia exposure and alterations in internal homeostasis[ 21 ].…”
Section: Discussionmentioning
confidence: 99%